Comparison of bone-anchored male sling and collagen implant for the treatment of male incontinence - Onur, Rahmi; Singla, Ajay (Blackwell Publishing, 2006)
Aim: To compare the effectiveness of transurethral collagen injection and perineal bone-anchored male sling for the treatment of male stress urinary incontinence (SUI). Methods: Seventy-one men with SUI underwent either transurethral collagen injections (n = 34) or perineal bone-anchored male sling (n = 37) between June 1999 and October 2003. Most of the patients in each group had radical retropubic prostatectomy and/or external beam radiation therapy (EBRT) in relation to the cause of incontinence. There was one patient in both groups who only had EBRT for the cause. The mean duration of incontinence were 4.2 and 4.4 years, respectively. Collagen injections were carried out transurethrally either under regional or general anesthesia until co-aptation of mucosa was observed. The male sling was placed under spinal anesthesia with a bone drill using either absorbable or synthetic materials. Retrospectively, all patients were assessed for continence status and procedure-related morbidity, if present. The outcome of both procedures was also compared with the degree of incontinence. Results: Ten (30%) patients in the collagen group showed either significant improvement or were cured following injections. Preoperatively, the mean pad use in collagen group was 4.5 (SD 2.8) per day, whereas it was 2.2 (SD 1.1) after the injection(s). Collagen injection failed in 24 (70%) of the patients. Patients who received the male sling had a mean preoperative pad use of 3.7 (SD 1.5) and postoperatively, the number decreased to 1.6 (SD 1.2). Most of the patients in this group were either totally dry or significantly improved (n: 28, 76%). There was a statistically significant difference between two groups in respect to success rate (P < 0.05). Analysis of treatment outcome with the degree of incontinence revealed that the male sling is most effective in patients with minimal-to-moderate incontinence. Conclusions: Our results suggest that the male sling, a minimally invasive procedure, is more effective than collagen implant in the treatment of mild-to-moderate SUI in men.
Keywords: collagen; comparison; incontinence; male sling